Antikrizisnyy monitoring of finansovo-ekonomicheskikh indexes of work of enterprise - Pererva, P. G.; Tovazhnyanskiy, Vyacheslav; Kobielieva, T. O.; Gladenko, Ivan (University of Miskolc, 2010)
In the article the questions of warning of the crisis phenomena are considered on machine-building enterprises. The complex of mathematical functions which design production and market situations on an enterprise is offered. The use of suggestions of authors will help machine-building enterprises to diagnose a crisis on his early stage, to carry out monitoring of innovative activity, design a market situation, forecast the market state of affairs.

У статті розглядаються питання попередження кризових явищ на машинобудівних підприємствах. Комплекс математичних функцій, дизайн виробничих і ринкових ситуацій, на підприємства. Використання пропозицій автора допоможе машинобудівних підприємств для діагностики кризи на ранній стадії, проводити моніторинг інноваційної діяльності, розробці ринкової ситуації, прогнозування стану ринку справ.
Антикризовий моніторинг фінансово-економічних показників роботи підприємства